The NArCoS Project: efficiency estimation and the cross talk problem studied through Monte Carlo simulations. (December 2020) - Pagano, E V; Auditore, L; Cardella, G; Filippo, E De; Geraci, E; Gnoffo, B; Lanzalone, G; Maiolino, C; Martorana, N S; Pagano, A; Papa, M; Pirrone, S; et al.
Abstract: With the advent of the new radioactive beam facilities it is necessary to develop neutron detection systems integrated with charged particle ones. The integration of the neutron signal, especially in using neutron rich beams, becomes a mandatory requirement in order to study the property of the nuclear matter in extreme conditions. For this reason new detectors using new materials have to be built. In this contribution, some new results about the efficiency estimation and the cross talk problem studied through GEANT4 simulations, related to the NArCoS project, will be described with the aim to design a new detector of both good energy and angular resolution. The detection of neutrons and charged particles in the same elementary detection cell is envisaged.